2017
DOI: 10.1002/cam4.1083
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of liposomal topotecan for use in treating neuroblastoma

Abstract: The purpose of this work was to develop an optimized liposomal formulation of topotecan for use in the treatment of patients with neuroblastoma. Drug exposure time studies were used to determine that topotecan (Hycamtin) exhibited great cytotoxic activity against SK-N-SH, IMR-32 and LAN-1 neuroblastoma human cell lines. Sphingomyelin (SM)/cholesterol (Chol) and 1,2-dis tearoyl-sn-glycero-3-phosphocholine (DSPC)/Chol liposomes were prepared using extrusion methods and then loaded with topotecan by pH gradient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
(68 reference statements)
0
10
1
Order By: Relevance
“…Interestingly, a different study from our laboratory showed that the in vivo release rate of topotecan from an optimized liposomal formulation [25] was 25% per hour, which was faster than the maximum release rate of 17% per hour (see Fig. 4c) demonstrated using the present in vitro assay.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, a different study from our laboratory showed that the in vivo release rate of topotecan from an optimized liposomal formulation [25] was 25% per hour, which was faster than the maximum release rate of 17% per hour (see Fig. 4c) demonstrated using the present in vitro assay.…”
Section: Discussioncontrasting
confidence: 53%
“…Comparing the cytotoxicity of topotecan to liposomal topotecan Given that the liposomal topotecan formulation retained drug over extended time periods [25], it was expected that the liposomal formulation would be less active in vitro when compared to free topotecan. The cytotoxicity of liposomal topotecan was compared to topotecan when tested on different cell lines and over different incubation times (Fig.…”
Section: Characterization Of the Liposomal Formulationsmentioning
confidence: 99%
“…Liposomes can penetrate some solid tumours by 'passive targeting' through the enhanced permeability and retention (EPR) effect 67 . Although this appears feasible in neuroblastoma xenograft models 68,69 , it is unclear whether EPR is relevant here clinically. The delivery of oxidovanadium complexes in vivo for neuroblastoma would likely need more advanced liposomal technology, such as tumour targeting with RGD-based peptides 60,69 , or antibodies specific for disialoganglioside 2 (GD2), a key antigen on neuroblastoma cells 70,71 .…”
Section: Discussionmentioning
confidence: 99%
“…Topotecan undergoes a pH-dependent, reversible hydrolysis into a nonactive carboxylate at physiologic pH (Devriese et al, 2015). With this in mind, a liposomal topotecan formulation was prepared to protect the cytostatic drug from this pH-induced hydrolysis (Chernov et al, 2017;Gilabert-Oriol et al, 2017). Pharmacokinetic studies showed that the nanoformulation exhibited a 10-fold increase in plasma half-life values in comparison with equivalent doses of topotecan (Hycamtin); however, encapsulated topotecan only modestly increased the life span of NB mice.…”
Section: Nontargeted Nanomedicines For Neuroblastomamentioning
confidence: 99%